Fengsel eller frihet: Noe om reaksjonsvalg i norsk strafferett - Morten Holmboe (Nordisk Tidsskrift for Kriminalvidenskab)
The grounds for a given society's punishment of offenders has a long history of discussion. In Norway, deterrence is seen as the basis for the criminal justice system - both in general and as a guide in choosing between types of punishment in concrete cases. General deterrence theory suggests that people might abstain from crime either because of an assessment of its potential risks or because the use of punishment leads to a general habit of obeying the law - and that people rest assured that justice is done, leading to a sense of safety in society.